HUBUNGAN EKSTRAKURIKULER PRAMUKA DENGAN KEDISIPLINAN SISWA SEKOLAH DASAR - Mahrani, Putri Aqilla; Nurmayani; Simanjuntak, Eva Betty; Gandamana, Apiek; Siregar, Waliyul Maulana (Universitas Negeri Medan, 2025)
The problem found in this research is the lack of student discipline, there are students who do not obey the rules, such as students arriving late, not wearing attributes, and playing around during ceremonies. This research aims to determine the significant relationship between scout extracurricular activities and the discipline of students at SD Negeri Kec. Stabat, Kab. Langkat T.A 2023/2024. The type of research used is quantitative research with correlational methods. From the research results, it was found that there was a significant relationship between scout extracurricular activities and the discipline of students at SD Negeri Kec. Stabat, Kab. Langkat. This is shown from the calculation of the Hypothesis Test using the t-test, obtained a value of 8.513 > 2.004, which means that Ha is accepted and Ho is rejected, so it can be said that there is a significant relationship between scout extracurricular activities and the discipline of students at SD Negeri Kec. Stabat, Kab. Langkat.